Melangkah Menuju Kesehatan Mental yang Optimal: Program Inovatif di Lembaga Pendidikan Islam - M. Mansyur; Rofiqi, Rofiqi; Iksan (Universitas Islam Negeri Madura, 2023)
Mental health education is an important aspect for students in schools, but is often neglected by educational institutions. Even though students often face high academic pressure, social demands, and emotional challenges, that can have a negative impact on their mental well-being, which also affects academic achievement. This study aims to provide alternative solutions regarding educational innovations that can be carried out in developing mental health education programs in educational institutions. The research method was carried out through Systematic Literature Review (SLR) using the Publish or Perish application as an instrument for identifying journal articles. Articles are obtained and eliminated based on the criteria of quality, novelty, and conformity with specific research themes. The results of this study indicate that mental health education has a significant role in the mental well-being of students at school. Therefore, mental health education innovations must be carried out in the context of developing school programs. Mental health education innovationsthat can be carried out include collaboration between Islamic educational institutions and professional staff, and integration of the health education curriculum with the school curriculum.